Survival Analysis of Criminal Recidivism of Boot Camp Graduates Using Elements From General and Developmental Explanatory Models - Benda, Brent B. (International journal of offender therapy and comparative criminology, 2003)
This is a 5-year follow-up study of recidivism among 601 male graduates of a boot camp for adults in a southern state. Cox's proportional hazard analysis is used to determine the hazard rate of recidivism (arrest or parole violation) of several elements of general and developmental models. Analyses are conducted according to age of onset of unlawful behavior (10 years old or younger and older than 10 years). Findings indicate that caregiving factors have inverse relations with the hazard of recidivism, whereas low self-control, deficits in social skills, peer association with criminals, gang membership, drug use and sales, and carrying weapons have positive relationships with this hazard. These findings are observed irrespective of the age when persons begin committing offenses. Implications of the findings for theoretical models is discussed